(untitled) (Journal of the College of Education for Women, 2019)
AbstractThe perpetuity of the Quranic discourse required being suitable for all ages.Accordingly, the method of the Glorious Quran a pre request for the consciousinvestigation and realization in order to detect the core of the texts, as the Quranicdiscourse is considered a general address for the humanity as a whole. For thisreason, the progress of the concerned studies neceiated that it should cope with thecurrent development in the age requirements and its cultural changes within ages.The texts of the Glorious Quran lightened the human reason as being theCreator’s miracle for it is characterized by certain merits that makes it different from poetry and prose. It is a unique texture in its rhetoric and composition. So, themodern studies in reading the Quranic text, there is specific spectacle, but there mustbe an analytical reading for its texts and investigating its components to reach to thevariety in its meanings and significations of its Quranic words.The language of the discourse or the architecture of the text and its geometrydepend on its textual construction composed of a group of different, topics andstyles. The latter has suggestive significations preparing the shades of meaningswhile it is in fact hidden and becomes apparent by the context and its situation.There are certain utterances that draw the picture of the text not by its decadnessbut by its shades and special suggestions that cannot be felt only by the expert.For this reasons, the present study came as an attempt to detect and show theaesthetics of the Quranic text, its miraculous geometry and its expressive andperforming power representing the rhythmic and phonological side. The latter is quiteapparent in the Quranic structure of every sura. Beside, it is a study that investigatesthe internal movement of the rhythm and suggestion of the utterances themselves.